Analisis Faktor Yang Dipertimbangkan Dalam Penentuan Nisbah Bagi Hasil Pembiayaan Mudharabah Dan Musyarakah Pada PT BANK BNI SYARIAH Cabang Jember - Lia Rachmawati; Wiwik Fitria Ningsih (STIE Mandala Jember, 2018)
The purpose of this study is to analyze the factors considered in determining the profit sharing ratio of mudharabah and musharaka financing in BNI syariah Ltd. Jember branch. This research uses positivistic paradigm with qualitative approach. Based on the results of the following research several factors into consideration in the determination of the ratio of profit sharing there are The system of sharing based on revenue sharing; Good relationship with customers; Amount of financing value; The business feasibility of the customers; Estimated customer turnover. Keywords: musharaka, nisbah, revenue sharing